The effects of the FOPI controller and time delay on stability region of the fuel cell microgrid - Ozdemir, Mahmut Temel (Pergamon-Elsevier Science Ltd, 2020)
In this paper, the effects of the time delay (t) and the order of the fractional integral (A) on the stable parameter region of the FOPI controller for a fuel cell microgrid is investigated. The stability boundary curves depending on A and t values of the fuel cell microgrid, i.e., stable parameters space of the FOPI controller, are obtained by using the stability boundary locus (SBL) method. The SBL is a graphical technique and in this technique, the stable regions of the system are obtained by using the characteristic equation of the system. The obtained stable regions are tested by the time-domain simulations and the generalized and modified Mikhailov (GMM) criterion. The effect of t and A on the stable parameter region of the FOPI controller for a fuel cell microgrid with time delay has been shown in the literature for the first time through this study. The obtained results show that t and A have considerable effects on the change of stable region. The results also show that the effect of A is much higher than the t0s effect. Therefore, it has been demonstrated that the effect of the large time delay, which makes the system unstable, can be reduced by A in this study. (c) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Fuel cell microgrid; Time delay effect; Fractional order PI Controller; Stability boundary locus